Explorative Perspectives in Music and Education - Buan Øien, Ola (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
The anthology Explorative Perspectives in Music and Education resulted from the MiU22 conference and seeks to support diverse dialogues. The publication, which is multimodal and interdisciplinary, explores how academic, artistic, and pedagogical research and performative work within the realm of music and education intertwine with the central theme. The anthology aims to objectively explore the intersection of performative, qualitative and quantitative research paradigms by bringing diverse artistic and research-based perspectives into dialogue. Notably, the anthology presents the first peer-reviewed video article in the MusPed:Research series, contributing innovative work. The book's 10 peer-reviewed research chapters on music and education focus on conceiving music and education concepts in different contexts.